EFFECT OF SOME FEEDING SYSTEMS AND HORMONAL TREATMENT ON REPRODUCTIVE PERFORMANCE AND LAMBS GROWTH IN AWASSI SHEEP - Khalid Sultan; SAEB ABDL-ALRHMMAN; Rathi Abdullah (Mesopotamia Journal of Agriculture)
The study was conducted on Eighty Awassi ewe lambs(10 month aged) to evaluate the effect of Grazing GR, Feeding frequency FF and hormonal treatment HT on ,reproductive performance and lambs growth, Estrous synchronization was conducted, Animal groups (10 ewes each ), 8 different treatments were applied including GR, FF, eCG and GnRH hormonal treatments. The results revealed that the Fertilization rate, Fertility%, Lambing % at weaning and Barrenness% were better significantly ( P≤0.01) in the 2nd treatment ( GR + ROD +PMSG ) , while the results of the 3rd treatment ( GR + RTD + PMSG & GnRH ) and 5th treatment ( without GR + ROD + PMSG & GnRH ) in Litter size ( Higher value ) and Abortion ( Lower value ) were better significantly than other groups, the higher mortality % of lambs was recorded in 6th treatment ( without GR + ROD + PMSG ) group. The results also revealed a significant increase in lambs BW in GR treatment at 12th week, and a significant increase in lambs birth weight in ROD treatment, while the best interaction effects in lambs weight were recorded in the 3rd treatment ( GR + RTD + PMSG & GnRH ) group at the 8th, 10th and 12th weeks and in the 6th treatment ( without GR + ROD + PMSG ) at the 6th week after lambing. The results also showed a significant increase in BG in ( GR ) group at the 10th and 12th weeks and in ( RTD ) group at the 8th week, while the best interaction effects on BG was recorded in the 1st treatment ( GR + ROD + + PMSG & GnRH ) group at 10th and 12th weeks after lambing .And in regard to milk production / day there is a significant increase in GR treatment at 6th and 12th weeks, and in (PMSG & GnRH ) treatment at 8th week, and the best interaction effects were recorded in the 3rd treatment (GR + RTD + PMSG & GnRH) group at 2nd , 4th , 6th , 8th , 12th weeks after lambing. In conclusion grazing enhanced feeding state and improved the reproductive performance of ewes and milk production for lambs growth.